2005
DOI: 10.1021/jp044629q
|View full text |Cite
|
Sign up to set email alerts
|

A Multiscale Coarse-Graining Method for Biomolecular Systems

Abstract: A new approach is presented for obtaining coarse-grained (CG) force fields from fully atomistic molecular dynamics (MD) trajectories. The method is demonstrated by applying it to derive a CG model for the dimyristoylphosphatidylcholine (DMPC) lipid bilayer. The coarse-graining of the interparticle force field is accomplished by an application of a force-matching procedure to the force data obtained from an explicit atomistic MD simulation of the biomolecular system of interest. Hence, the method is termed a "m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
1,249
0
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 1,080 publications
(1,283 citation statements)
references
References 17 publications
10
1,249
0
1
Order By: Relevance
“…It has been empirically demonstrated that even for highly complex systems the MS-CG method generates a useful and quantitatively accurate model. 16,17,[24][25][26][27][28]46 …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been empirically demonstrated that even for highly complex systems the MS-CG method generates a useful and quantitatively accurate model. 16,17,[24][25][26][27][28]46 …”
Section: Discussionmentioning
confidence: 99%
“…17 The CG force field is obtained by minimizing a residual describing the difference between the instantaneous forces defined by the CG force field and the original atomistic force field. This difference is statistically averaged over all CG sites and all configurations sampled from the atomistic MD simulations.…”
Section: Many-body Cg Potential Of Mean Forcementioning
confidence: 99%
See 3 more Smart Citations